ESPEN practical guideline: Clinical nutrition in chronic intestinal failure. Issue 9 (September 2021) - Cuerda, Cristina; Pironi, Loris; Arends, Jann; Bozzetti, Federico; Gillanders, Lyn; Jeppesen, Palle Bekker; Joly, Francisca; Kelly, Darlene; Lal, Simon; Staun, Michael; Szczepanek, Kinga; Van Gossum, André; et al.
Summary: Background: This practical guideline is based on the ESPEN Guidelines on Chronic Intestinal Failure in Adults. Methodology: ESPEN guidelines have been shortened and transformed into flow charts for easier use in clinical practice. The practical guideline is dedicated to all professionals including physicians, dieticians, nutritionists, and nurses working with patients with chronic intestinal failure. Results: This practical guideline consists of 112 recommendations with short commentaries for the management and treatment of benign chronic intestinal failure, including home parenteral nutrition and its complications, intestinal rehabilitation, and intestinal transplantation. Conclusion: This practical guideline gives guidance to health care providers involved in the management of patients with chronic intestinal failure.